Understanding Democratic Engagement at the Micro-Level: Communication, Participation and Representation - Moug, Peter (My University, 2008)
Theoretical and ‘real world’ research into democratic engagment concentrates on larger-scale contexts. There is an accompanying tendency to focus on participation, neglecting other aspects of engagement. The thesis rethinks the notion of democratic engagement by dividing it into three analytically distinct, but interwoven, aspects namely communication, participation and representation, and drawing attention to small-scale or micro-level contexts. Understanding the communicative, participative and representative aspects of engagment in micro-level settings favours a case study approach and a research strategy designed to capture the minutiae of experiences of engagement. ‘Mossbank’, a neighbourhood in a small-to-medium sized Scottish town, has been chosen as an appropriate case. Mossbank is undergoing a physical and social regeneration initiative that has created new sites of democratic activity centred on Mossbank-related issues. It is also a setting where democratic engagement is likely to be constrained. A flexible mixed methods approach to data collection has been adopted using questionnaires, interviews, documentary analysis and non-participative observation, enabling the generation of ‘rich’ and ‘thick’ data. A theoretically informed analytical framework is used to explore the different aspects of democratic engagement in Mossbank. Here, Iris Marion Young’s theorising on communication in deliberative settings has been particularly influential. Democratic engagement in Mossbank is dominated and constrained by formal, familiar and broadly conventional institutions, processes and roles ‘imported’ from established larger-scale democratic settings. Less visible, context-specific factors also have an influence. ‘Messy’ practices and asymmetry affect the ‘quality’ of communication. Participation in democratic processes has its own particular constraining characteristics related to individual motivations and abilities to ‘fit in’ and ‘succeed’ within pre-existing processes. Representation in Mossbank is distant and sporadic, culminating in the evolution of an increasingly brokered approach to the relationship, administered by an intermediary. The thesis contributes to ‘empirical’ debates relating to the scope and nature of democratic engagement. This is especially relevant given the continued growth and development of micro-level democratic institutions and processes in developed democracies. The thesis also contributes to debates concerning the nature and extent of the ‘dialogue’ between normative ideals of democracy and engagement, and research into ‘real world’ democratic engagement.
Keywords: politics; democratic engagement